PENGELOLAAN PEMBELAJARAN AKIDAH AKHLAK DENGAN MEDIA PEMBELAJARAN CD INTERAKTIF - Almaida Almaida (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to determine the learning process of Aqidah Akhlak with interactive CD learning media. This is done because students have low interest and motivation in learning the subjects of Aqidah Akhlak in the madrasa. This study uses classroom action research conducted in two cycles consisting of three stages, namely: planning, implementation and reflection. The target of this study was a fifth grade student at State Islamic Middle School I, Meulaboh West Aceh. The research sample consisted of 18 students who followed the learning process. From the results of the analysis it was found that: 1) student learning completeness in the first cycle of student learning completeness was lower than the standard set, 2) in the second cycle students' learning completeness reached 68.75% exceeding the standards set. Thus, it can be said that the improvement in the increase in interest and motivation of students in Aqidah Akhlak lessons can be done with interactive CD media with various improvements to the obstacles and problems that occur in practice in the classroom. Keywords: Aqidah Akhlak Learning, Learning Media, Interactive CD, Madrasah